Hubungan Self-Efficacy dengan Tingkat Kepuasan Kerja Perawat - Lusi Nurlita; Solehudin Solehudin; Sancka Stella G. Sihura (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Self-efficacy is a psychological factor that plays an important role in shaping nurses’ work attitudes and behaviors, including job satisfaction. Nurses’ job satisfaction affects the quality of nursing care and workforce sustainability in hospitals. This study aimed to determine the relationship between self-efficacy and job satisfaction among nurses at FMC Hospital in 2025. This study employed a quantitative correlational design with a cross-sectional approach. The sample consisted of all actively working nurses at FMC Hospital, totaling 83 respondents, selected using a total sampling technique. Data were collected using the General Self-Efficacy Scale (GSES) and the Job Satisfaction Survey (JSS). Data analysis was conducted using univariate and bivariate analyses with the Spearman Rank correlation test. The results showed that most nurses had a high level of self-efficacy (98.8%), and all respondents were categorized as satisfied with their jobs. The Spearman Rank correlation test revealed a significant positive relationship with a moderate strength between self-efficacy and job satisfaction (ρ = 0.415; p < 0.001). In conclusion, higher self-efficacy is associated with higher job satisfaction among nurses. Therefore, strengthening nurses’ self-efficacy should be considered an important strategy in hospital human resource management.